Pinças ópticas: experimento, teoria e aplicação no estudo da interação DNA-fármacos - Marcio Santos Rocha (2008)
We started this work studying the physics of optical tweezers. This isa micromanipulation technique much used to study particles and biological systems with size in the micrometer range. We theoretically analyze the phenomenon and apply experimental techniques to verify the results of a recent theory of optical tweezers, the MDSA Theory. We measure the trap stiffness of the optical tweezers as a function of the trapped bead radius. These experimental results show a good agreement with the predictions of the MDSA Theory. This comparison does not involve any adjustable parameter: all parameters of our optical tweezers, necessary to obtain the theoretical results, were precisely measured. Therefore, the comparison between experiments and theory is called absolute. Next, we apply the optical tweezers technique, combined with the intensity autocorrelation spectroscopy technique, to study one of the most important biological systems: the DNA molecule. With these two techniques, it was possible to study the interaction of the DNA molecule with some important medicinal drugs, much used in the treatment of human diseases. We have performed stretching experiments with DNA molecules and DNA-drugs complexes. These experiments allow us to study the entropic elasticity and size variations of these complexes. We found a new structural transition of the DNA molecule, induced by these drugs, measuring the persistence lengthof the complexes as a function of the drug concentration in solution. These results have contributed to clarify the DNA-drugs interaction, and also the mechanical properties changes of the DNA molecule induced by these drugs.